UiTM News Hub: Innovative Educators of Academy of Language Studies (APB), UiTM Perlis Branch showcase their expertise at i-VISION 2021 / Dr. Latisha Asmaak Shafie, Nurul Alia Nafis Najmi and Dr. Razlina Razali - Shafie, Latisha Asmaak; Najmi, Nurul Alia Nafis; Razali, Razlina (2021)
International Virtual Symposium on Innovation and ELT 2021 (i-VISION 2021) was organised by Darul Aman English Language Learning and Teaching Association (DELTA) on 13 and 14 December 2021. The theme for i-VISION 2021 was "Enhancing the Dynamics of Teaching through Innovation: Reinforcing Impactful Delivery". i-VISION 2021 invited selected presenters who were award-winning innovators to highlight their innovations and share their expertise.